Convergence in GDP per capita across the EU regions— spatial effects - Pietrzykowski, Maciej (Economics and Business Review, 2019)
The aim of this paper is to offer an empirical insight into the spatial effectsof growth of regional income and disparities across EU regions (NUTS 2). Since regionsare spatial units and there are interrelated standard linear regression is not sufficientto evidence the convergence process. Two models (Spatial Lag Model – SLMand Spatial Error model – SEM), derived from spatial econometrics, have been usedto identify and explain spatial effects in convergence clubs—all EU countries (EU-28),countries that entered the EU in 2004 (EU-13) and countries that were in EU prior to2004 (EU-15). Unconditional and conditional β-convergence has been examined inthe period 2000-2015 thus covering two financial perspectives (including n + 2 rule3).Dummy variables have been also applied to catch the country-specific effects, such asnational policies, legislation, technology progress, etc.